ISOLASI MANNAN DARI DAUN LIDAH BUAYA (Aloe vera) DENGAN PROSES EKSTRAKSI SEBAGAI BAHAN DASAR PEMBUATAN EDIBLE COATING BERBASIS POLISAKARIDA - Mutia Istianah; Sumarlin Mahadi Putra; Diah Susetyo Retnowati (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Aloe veraleap pulp contains polysaccharide ,organic and other inorganic materials. Many benefits of aloe vera so it is needed to explore the potential that exists in the aloe vera plant. Extraction process and deposition was method to take an active substance (mannan) contained in aloe vera. In this process the fixed variable are 200 grams of Aloe vera pulp, extraction temperature at 40 0C, and the ratio of ethanol: mannan solution = 3:1. While the independent variables used are the weight ratio (g) of  Aloe verapulp to distilled water solvent (1:2, 1:3, 1:4, 1:5), and the extraction time used (30, 45, 60, 75) minutes . Extracted mannanincrease as Aloe vera leaf pulp or aquadest ratio and extraction time are increase. Similarly, the extraction time, then the extracted Mannan also will be many more ..